2022
DOI: 10.3390/en15051904
|View full text |Cite
|
Sign up to set email alerts
|

Study on Combustion Characteristics of Cable Based on Cone Calorimeter

Abstract: Cross-linked polyethylene (XLPE) carries a high fire risk. In this paper, a cone calorimeter is used to carry out radiation ignition experiments, and the heat release rate (HRR), mass loss rate (MLR) and other combustion parameters of XLPE cables under three kinds of radiation intensity are measured. By comparing the ignition time and HRR of samples under different conditions, the following conclusions are drawn: (1) The ignition time of XLPE cables decreases significantly with the increase in external thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…As indicated in the pHRR curves of 1.5, 2, 2.5, and 3 I e , these wires damaged by various currents require nearly the same time to reach at pHRRs, which are approximately identical. Similar to the thermal aging PVC copper wire [ 7 , 15 ], the wire overloaded at 3.5 I e requires more time to increase its pHRR, which is lower than that of other overloaded wires exposed to various external heat fluxes. This result likewise indicates the 3.5 I e flowing through the PVC copper wires can deteriorate the active composition and structure of polymer insulation materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated in the pHRR curves of 1.5, 2, 2.5, and 3 I e , these wires damaged by various currents require nearly the same time to reach at pHRRs, which are approximately identical. Similar to the thermal aging PVC copper wire [ 7 , 15 ], the wire overloaded at 3.5 I e requires more time to increase its pHRR, which is lower than that of other overloaded wires exposed to various external heat fluxes. This result likewise indicates the 3.5 I e flowing through the PVC copper wires can deteriorate the active composition and structure of polymer insulation materials.…”
Section: Resultsmentioning
confidence: 99%
“…Meinier et al [ 6 ] studied the fire performance of halogen-free flame-retardant electrical cables with a cone calorimeter and discussed the influence of two parameters, namely, external heat flux and the spacing between cables. Zhang et al [ 7 ] measured combustion parameters, such as the heat release rate (HRR) and mass loss rate of cross-linked polyethylene (XLPE) cables under three radiation intensities. Hirschler [ 8 ] and Barnes [ 9 ] studied the combustion behavior of a series of cables based on ISO 5660 and ASTM d5424 [ 10 ] using a cone calorimeter.…”
Section: Introductionmentioning
confidence: 99%
“…Combustion behavior of power cables studied using a cone calorimeter [ [14] , [15] , [16] ]. Numerous studies have shown that cables under such fire test equipment have the following characteristics [ [17] , [18] , [19] , [20] ].…”
Section: Experimental Descriptionsmentioning
confidence: 99%
“…Some of these were performed at a reduced scale, mainly using cone calorimeter. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] The idea is to reduce the scale to ease the study of such complex configurations and to find correlations between the behaviour of the cables at reduced and real scales. However, although these studies provided valuable knowledge, experiments at a real scale remained unavoidable due to the complexity of the problem and the multitude of interactions involved.…”
Section: Introductionmentioning
confidence: 99%